Construct validity and reliability of the skills Self-concept Scale of MC Dayton - Merino Soto, César (2003)
The present article report about the construct validity and internal reliability of the Self concept of Ability scale (Dayton, 1968), that measure the perception of the student's academicabilities in the school class, it based on the comparisons that make those against references external. Recently, the theoretical model proposed by Marsh and Craven (2002), on the self-concept academic based on the external references, it directs the objective of the present study, because to their direct relationship between this model and the instrument of Dayton. Applying a confirmatory factorial approach with correlated factors, in a sample of 97 students, the preliminary findings point out that the multidimensional model is fit appropriately to the data. The reliability of the subscales is quite good. Although these results suggest stability in the factorial solution, studies of cross-validation of this potential instrument are required.